2010
DOI: 10.1103/physrevlett.105.227802
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Driven Enhanced Self-Diffusion in Confined Reentrant Supernematics

Abstract: We present a molecular dynamics study of reentrant nematic phases using the Gay-Berne-Kihara model of a liquid crystal in nanoconfinement. At densities above those characteristic of smectic A phases, reentrant nematic phases form that are characterized by a large value of the nematic order parameter S≃1. Along the nematic director these "supernematic" phases exhibit a remarkably high self-diffusivity, which exceeds that for ordinary, lower-density nematic phases by an order of magnitude. Enhancement of self-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…Molecular dynamics simulations on rod-like systems have successfully contributed to a more detailed understanding of the isotropic-to-nematic transition in confinement [38,41,[64][65][66]. In fact, a recent molecular dynamics study documented radial movements of phase fronts analogous to the ones inferred here, however for a rod-like system in nanochannels [44].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Molecular dynamics simulations on rod-like systems have successfully contributed to a more detailed understanding of the isotropic-to-nematic transition in confinement [38,41,[64][65][66]. In fact, a recent molecular dynamics study documented radial movements of phase fronts analogous to the ones inferred here, however for a rod-like system in nanochannels [44].…”
Section: Discussionmentioning
confidence: 53%
“…However, similarly as the dynamical and structural behavior of rod-like liquid crystalline systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47], the properties of DLCs has turned out to be particularly susceptible to nano confinement [27][28][29][30][31][32][48][49][50]. Thus, new, simple experimental methods that are able to monitor the type of molecular ordering inside nanoporous media are strongly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the present authors recently studied a model system of rod-like LC with molecular dynamics (MD) simulations [23,24]. We showed that as P is raised the usual sequence of phase transitions isotropic → nematic → smectic A is followed by a RN phase.…”
Section: Introductionmentioning
confidence: 97%
“…The RN phase exhibits a self-diffusion coefficient significantly larger than in the nematic phase. It was shown that the self-diffusion coefficient in the direction of the nematic director varies inversely proportional to the width of the distribution of molecular orientations or, in other words, the decrease in orientational entropy in the RN phase leads to an enhanced diffusivity [23]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to these static effects, diffusion of liquid crystals in nanoconfinement is also quite unique. 29 We have focused here on planar surfaces. An interesting aspect of flexible surfaces such as lipid membranes is that they can wrap around adhesive particles.…”
mentioning
confidence: 99%